Internal framework and geochemistry of the Carboniferous Huaco granite pluton, Sierra de Velasco, NW Argentina - Sardi, Fernando Guillermo (2018)
The A-type Huaco granite pluton of the Velasco range (Sierras Pampeanas of northwest Argentina) is formed by three coeval granitic facies and contains subordinate coeval-to-late facies, as well as enclaves, dikes and stocks that show different temporal relations, textures and compositions. The dominant facies (Regional Porphyritic Granite; RPG) is a porphyritic two-mica monzo- to syenogranite, with abundant microcline megacrysts up to 12 cm in size. It was emplaced in a dominant extensional setting and has a mainly crustal source but with participation of a mantle-derived component. The RPG transitions towards two coeval and co-genetic granite facies, at its margins (Border Granite; BG) and around Be-pegmatites (Adjacent Porphyritic Granite; APG). These two facies have a finer-grained texture and smaller and less abundant megacrysts. They are also monzo- to syenogranites, but a slight decrease in the biotite/muscovite ratio is observed from the BG to the RPG to the APG. Trace element modeling suggests that the RPG, BG and APG differentiated from the same magma source by fractional crystallization. Temporally older mafic (ME) and felsic (FE) enclaves are common in the pluton. The ME can be considered partially assimilated remnants of a mafic component in the genesis of the RPG, whereas the FE seem to be remnants of premature aplites. Other subordinate rocks intrude the RPG and are, hence, temporally younger: felsic dikes (FD), dioritic dikes (DD) and equiganular granites (EqG) are clearly posterior, whereas coeval-to-late Be-pegmatites (BeP) and orbicular granites (OG) formed during the final stages of crystallization of the pluton. The BeP, OG and FD indicate the presence of abundant water and volatiles. The EqG form small stocks that intrude the RPG and were possibly originated from purely crustal sources. The DD probably correspond to a younger unrelated episode of mafic magmatism.